Integrating the SECI Model into Knowledge Management Practices in Elementary Schools - Purnamawati, Risa Fahriyani; Hidayat, Rais (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Knowledge Management (KM) is an essential strategy for improving organizational performance in a highly competitive and ever-changing landscape. This research investigates the application of the SECI Model, which stands for Socialization, Externalization, Combination, and Internalization, is a framework for understanding knowledge creation and management. within KM and its impact on individual performance at the Integrated Islamic Elementary School Darul Fallah in Bogor Regency. The study includes surveys to assess the effectiveness of KM strategies, utilizing an instrument with reliability scores ranging from 0.61 to 0.71. The findings reveal that the Internalization dimension significantly impacts individual performance (r = 0.72, p < 0.05) and accounts for 52% of performance variability (R² = 0.52), followed by Socialization (mean score = 4.10). Despite challenges such as limited time, staff resistance to knowledge sharing, and inconsistencies in documentation, KM implementation has led to improved learning innovation, administrative efficiency, and teacher collaboration. This study highlights the need for targeted training, a strengthened collaboration culture, and a user-friendly documentation system to optimize KM practices. The study adds to the current body of literature by providing empirical evidence on the importance of the SECI Model dimensions within the realm of primary education. Practical recommendations are offered to policymakers and administrators to foster a knowledge-sharing culture and enhance organizational performance. Future research should explore the application of the SECI Model across various educational contexts and levels to evaluate its broader effectiveness.